2008
DOI: 10.2137/145960606780061452
|View full text |Cite
|
Sign up to set email alerts
|

Abatement costs for agricultural nitrogen and phosphorus loads: a case study of crop farming in south-western Finland

Abstract: Designing efficient agri-environmental policies for agricultural nutrient load reductions calls for information on the costs of emission reduction measures. This study develops an empirical framework for estimating abatement costs for nutrient loading from agricultural land. Nitrogen abatement costs and the phosphorus load reductions associated with nitrogen abatement are derived for crop farming in south-western Finland. The model is used to evaluate the effect of the Common Agricultural Policy reform current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…by Lankoski and Ollikainen 1999, Iho 2005and Helin et al 2006. However, the emphasis in these studies is in theoretical set-up and crop production and their results are not directly comparable to this study.…”
Section: Review Of Literaturecontrasting
confidence: 59%
“…by Lankoski and Ollikainen 1999, Iho 2005and Helin et al 2006. However, the emphasis in these studies is in theoretical set-up and crop production and their results are not directly comparable to this study.…”
Section: Review Of Literaturecontrasting
confidence: 59%
“…Söderqvist and Scharin (2000) found that in the Stockholm archipelago a onemeter improvement in clarity from 1.5 to 2.5 meters, would require approximately a 30 percent reduction in nitrogen, while a similar improvement from a better initial water clarity of 2.5 meters would require a smaller, 21 percent reduction. Helin et al (2006) estimated that a 50 percent reduction in nitrogen flow from Finnish agriculture to the Gulf of Finland would cost 34.9 to 47.6 million euros annually, depending on policy regime. Although inland water eutrophication is more often phosphorus-limited, our simple water clarity models suggest that reductions in nitrogen flows to the sea also have an effect on inland waters, providing additional benefits.…”
Section: Comparison With Costsmentioning
confidence: 99%
“…We used the same nutrient and herbicide loading models as Lankoski et al (2006), compiled from a number of natural science studies, but abstracted away from buffer strips as a measure to mitigate loading. The nutrient model has also been applied by Helin et al (2006 (2006) or Helin et al (2006).…”
Section: Environmental Impact Simulationmentioning
confidence: 99%
“…The resulting reduction in environmental damage would be 45%, as opposed to the 34% obtained with the predicted use of fertilizers and plant protection products. For the parameters from Helin et al (2006), the analysis based on observed values would indicate that no-till reduces the total environmental damage. Here the simple approach thus yields results that are both quantitatively and qualitatively misleading.…”
Section: The Impact Of Tillage Technology On Nutrient and Herbicide Rmentioning
confidence: 99%